Pathways to Sustainable Welfare: Inertia, Emergence and Transformation in Swedish Cities - Emilsson, Kajsa; Fritz, Martin; Hildingsson, Roger; Johansson, Håkan; Khan, Jamil; Koch, Max (BECC: Biodiversity and Ecosystem services in a Changing Climate, 2025)
Cities face the challenge of providing welfare within planetary boundaries. As climate change accelerates and has led to a phase of climate emergency, more efforts are needed to handle the dual challenge of adapting to climate change while safeguarding the welfare of citizens. Through original empirical research, this academic work explores whether Swedish metropolitan cities – Gothenburg, Malmö and Stockholm – have entered the path towards sustainable welfare in urban governance. It examines integration across environmental and welfare domains in three core sites of urban governance – local government, civil society and public opinion. The book develops an original framework to capture stability and change by exploring theories in sociology, political science and sustainability studies. Guided by the concepts of inertia, emergence and transformation, the authors reveal that while cities largely adhere to established practices, keeping environmental and welfare concerns separate, promising signs of change emerge. These ‘seeds of emergence’ come from path entrepreneurs who are developing new ideas and practices for more sustainable, welfare-oriented modes of urban governance. The research finds them challenged by discourses and practices of rejection and denial, making it clear that a path towards sustainable welfare in urban governance remains contested.